A sensitive electrochemical sensor for nitenpyram detection based on CeO2/MWCNTs nanocomposite - Ai, Jixing; Wang, Xin; Zhang, Yan; Hu, Huali; Zhou, Huanxi; Duan, Yu; Wang, Dexiang; Wang, Hong; Du, Haijun; Yang, Yang (Applied physics. A, Materials science & processing, 2022)
Neonicotinoid insecticides are widely applied to improve the quality and yield of the crop. A sensitive and highly selective electrochemical sensor is required for monitoring their residues. In this paper, nano-structured cerium oxide and multiwall carbon nanotube composite (MWCNTs) were successfully constructed as an electrochemical sensor for nitenpyram (NIT) determination. The developed sensor has a broad linear range from 2 to 180 μM and a low detection limit of 0.72 μM (S/N = 3) for NIT detection under the optimal ratio of 1:1 between CeO 2 and MWCNTs. The electrochemical oxidation process of NIT involves one proton and two electron. Moreover, this developed sensor has excellent reproducibility with a relative standard deviation (RSD) of 3.1% in six replicated measurements, and excellent stability with 92.95% current retention after 15 days. In addition, the modified electrode has a good sensitivity and stability for the measurement of NIT in actual samples, it has the recovery ranges of 90.60–97.78% for the determination of NIT in corn extraction and 90.06–114.4% for that of NIT in river water. The proposed CeO 2 /MWCNTs sensor exhibits a great potential for the quick detection of neonicotinoid insecticides in the agricultural industry.